PENGEMBANGAN DAN VALIDASI METODE ANALISIS PENENTUAN KADAR ASAM FERULAT DALAM SERUM WAJAH - Ilma Shafira, Ahda
Ferulic acid or 4-hydroxy-3-methoxycinnamic acid is one of the most common phenolic compounds in plants. It has various activity including antimicrobial, antiarrhythmic, anti-inflammatory, antithrombotic, anticancer, antidiabetic, and antioxidant. As an antioxidant, ferulic acid is widely used in the cosmetic industry for skin care products with anti-aging claims. The increasing use of anti-aging has led to the development of anti-aging products, including anti-aging products made from ferulic acid. Therefore, a method that can determine the content of ferulic acid in the product was needed so that the quality, safety, and efficacy of the product can be maintained. This research was conducted to develop a method for determining ferulic acid content in serum products using High Performance Liquid Chromatography (HPLC). The research was started by optimizing mobile phase ratio, system suitability test, and method validation including specificity, linearity, intraday and interday precision, and accuracy. Based on the optimization results, acetonitrile: 0,1% (v/v) phosphoric acid (40:60) was used as mobile phase, with isocratic method, Fortis C18 column as the stationary phase, injection volume of 10 µl, flow rate of 1 mL/min, and wavelength of 319 nm. Linearity parameter is showed by correlation coefficient value of 0,9992 with a coefficient of variance of 2.382%. The detection and quantification limits of ferulic acid were also obtained at 0,009 µg/mL and 0,027 µg/mL. For intraday and interday precision, the relative standard deviation values were 0,163%-0,174%, and 0,153%-0,398%. The recovery for accuracy was in the range of 102,423 –108,185%. The method was then used to determine the levels of ferulic acid in the samples and the results were 0,143%, 0,172%, and 1,609%, respectively.